Roles of financial ratios to predict stock return: A study on Malaysian Construction Companies / Nasiha Hashim - Hashim, Nasiha (2017)
Financial ratios have been used expendably by many researcher as a variables to measure the prediction on stock return in many countries. So, this study is to know how financial ratios will affect the prediction on stock return in Malaysia Construction Companies that have been listed in Bursa Malaysia. The data is collected from datastream which consist of 108 construction companies in Malaysia during the year 2011-2015 (5 years). The data has been run using Eviews 9.5 software and the data is analyzed through descriptive test, normality test, stationary test, pooled least square, autocorrelation, fixed effect and also random effect respectively. In summary, the result showed that only return on assets has significant relationship with stock return while debt to equity, dividend yield, earnings yield and book to market value are not significantly influenced the prediction on stock return